Can organizational focus on responsible AI lead to improved AI adoption by employees? - CHOKSHI, Seema (Institutional Knowledge at Singapore Management University, 2024)
The duality inherent in Artificial Intelligence technology entails that while AI has the potential to bring about transformative benefits to organizations, unintended consequences of AI applications could lead to biased and discriminatory outcomes, which could have negative consequences for the organization and society in general. Concerns about such unintended consequences are an impediment to AI adoption where unwilling employees and practitioners often fear ethical breaches, thereby, negatively impacting their engagement with AI driven applications. In response to these concerns various organizations and regulatory bodies have developed governing frameworks broadly known as Responsible AI standards, that set guidelines to design, develop, and deploy ethical AI. My research is focused on studying the impact of ethical AI factors on professionals’ intentions to work alongside AI and explore the mechanisms behind this relationship. I have drawn linkages with literature, on Technology Acceptance Model, that specifies the factors that impact the technology usage intentions, namely perceived ease of use and usefulness of the new technology. This study is conducted at the individual employee level as professional employees are important stakeholders that contribute towards the success or failure of any organizational initiative. Employees’ perception of their organization’s social responsibility inversely moderates this relationship; results suggest that when the CSR perceptions are low, positive effect of ethical AI factors on usage intentions is strengthened. This study can benefit management in achieving organizational goals by leveraging the full potential of AI through improved employee engagement.